Potential of the Ethyl Acetate Extract of Kesambi (Schleichera oleosa) Bark as an Ointment-Based Treatment for Skin Diseases Against Staphylococcus aureus - Juliandoz; Dzulhijar; Boima Situmeang; Nani Yulianti; Nurhayati Bilangi; Weny Junus Abdul Musa; Mervina Rondonuwu; Sekar Ayu Ningrum (Jurnal Riset Sains dan Kimia Terapan, 2025)
One plant with potential to treat skin diseases is the Kesambi plant. Based on community experience in Cilegon, a decoction of Kesambi tree bark has been used to treat skin ailments, including itching, insect bites, and scabies. This research aims to reveal the potential of ethyl acetate extract from the tree bark as a standardized ointment preparation. Extraction was performed using the maceration method. Quality testing of the ointment included antibacterial, safety, stability, organoleptic, and bioactive compound content testing. The best formulation was formulation 1, with an antibacterial inhibition zone of 0.6-0.7 mm, classified as moderate. Increasing the amount of extract did not significantly affect antibacterial activity. The bioactive compound content in the ointment consisted of compounds from the groups of triterpenoids, steroids, phenolics, and flavonoids.